Leadership-Followership Concept: A Study Of Key And Supportive Terms In The Holy Qur'an - Diar Mahmood Saeed
This study aims to elucidate the concepts of leadership and followership from the Qur'anic perspective. In addition, a contextual and linguistic study of the key terms pertaining to leadership and followership will be presented. A comparative analysis of the meanings of leadership and followership in western writings and the Holy Qur'an was carried out. This study also explores the relevance of the concepts of leadership and followership in restoring the former glory of the Islamic civilization. The study mainly relies on library-based sources of data, which includes Qur'anic interpretations, and political sources. The researcher applies the thematic induction method for extracting the key terms from Qur'anic verses, and classifying them according to the subject. The researcher also uses descriptive analytical methods for analyzing the key terms, and the ways in which they were derived. Furthermore, the concept of followership from the Islamic perspective was compared to that put forth by western theorists. This study differs from previous studies in terms of the methodology, subjecting the key terms to linguistic and contextual examination, and its unique contribution to the field. The researcher supports findings related to the origins and historical development of leadership and followership with evidence &om the Qur'an, classical and contemporary literature. The study identifies a total of twenty four key terms of leadership that cover the family, social, economic, political and religious domains. On the other hand, existing literature documents a mere six key terms. A total of eleven types of followers were identified by the researcher in the Qur'an. This study is perhaps the first of its kind to analyze Kellerman's types of toxic leadership in light of the Qur'an. Last but not least, this study offers a detailed examination of the role of nurturing environments in preparing competent leadership that will restore the qualities of moderation and benevolence of the Ummah.